Neurophysiology of milk ejection and prestimulation in dairy buffaloes - Napolitano, Fabio (2022)
The present review aims to integrate the anatomical characteristics of the mammary gland and the neurophysiology of milk ejection to understand the milking capacity of the water buffalo. Since one of the main uses of this species is milk production, this article will analyze the controversies on the use of oxytocin as a stimulant during milking as well as the existing alternatives that farmers apply to promote correct stimulation during milk letdown. According to the available literature, the efficiency of the milking process, the quality of the milk, and the health of the animals are elements that require the consideration of species-specific characteristics to enhance the performance of buffaloes. The incorporation of technological innovations and competitive strategies could contribute to a better understanding of water buffalo in the milk industry.